PENYULUHAN PANGAN SEHAT DAN BAHAN TAMBAHAN PANGAN (BTP) BAGI SISWA SMP NEGERI 5 JAYAPURA, KOTA JAYAPURA - Abulais, Diana; Dianingsih , Nurlita; Numberi, Yulindra M; Keiluhu, Henderina J.; Suyono, Ign. Joko; Wambrauw , Daniel Z.K. (LPPM Uncen, 2024)
In Indonesia, the food industry has grown rapidly. Along with the development of the food industry, many negative impacts are caused, such as the circulation of food additives (FA) that are harmful to health. In practice, here are still many food industry that use hazardous FA which actually should not be used in food. Borax is useful for preserving wood and cleaning agents while formalin is a preservative for corpses and is carcinogenic which can trigger cancer if consumed. The use of rhodamine B in food for a long time leads to liver dysfunction or cancer, and when exposed to large amounts over a short period, it results in acute poisoning. Meanwhile nitrite can become hazardous if they form nitrosamines, and many can increase the risk for cancer. Based on the data of Extraordinary Events (KLB) of school snacks in 2017, food poisoning mostly occurred in elementary and junior high school students. Therefore, it is necessary to hold counseling to provide information to children about healthy food and the importance of knowledge about food additives, especially food additives that are harmful to health (borax, formalin, nitrite and rhodamine B). The results of the counseling showed good participant satisfaction, this was indicated by an increase in the percentage of student evaluation results.